Analiz rezultatov vystuplenij sbornoj komandy Rossii po sportivnoj gimnastike na Chempionate Evropy v Gretsii v aprele 2002 g. - Zarina, T. R. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
About the results of the Russian gymnastis at the European Championships 2002. With conclusions for the future development of gymnastics in Russia.